Pembuatan Mekanisme Strategi Perang pada Game Majapahitâs Conquest - Muliawan, Jimmy; Budhi, Gregorius Satia; -, Liliana (Jurnal Infra, 2015)
In order to make a visual media that can make student to take interest in history, game based learning is one of the solutions. The game first must have all aspect of the history itself in order to fulfill the goal. In this research, game that can cover the politic aspect especially war is made. The game will cover the politic aspect of Majapahit Kingdom and entitled Majapahitâs Conquest.This game use Turn Based Tactical as the genre which player and computer side moves his troops turn by turn. 2 methods of AI will be used in this game, which are Minimax and Fuzzy State Machine. This game will be made with Unity Engine, and scripting language will be done with C# as the language and MonoDevelop as IDE.The experiment is conducted to check the game system that support the war strategy of the game such as attack command or move/run command. The result of the experiment declare that all configured variables in troops influence the sytem.